Windmill-shaped octanuclear ZnII4/LnIII4 (LnIII = Dy, Tb, Ho) heterometallic ensembles supported by a tetraferrocene scaffold. Issue 44 (17th October 2016) - Chakraborty, Amit; Goura, Joydeb; Bag, Prasenjit; Bar, Arun Kumar; Sutter, Jean-Pascal; Chandrasekhar, Vadapalli
Abstract : Utilizing a new ferrocene-based compartmental ligand, H4 L (1 ), a series of novel heterometallic complexes [LZn(μ-OAc)Dy4 (μ4 -H2 O)] (2 ), [LZn(μ-OAc)Tb4 (μ4 -H2 O)] (3 ), [LZn(μ-OAc)Ho4 (μ4 -H2 O)] (4 ), [L = Fe[(C5 H4 )–C(Me){N–N{C6 H3 -( o -O)( m -O)]2 ] were synthesized and characterized. Abstract : Utilizing a new ferrocene-based compartmental ligand, H4 L (1 ), a series of novel heterometallic complexes [LZn(μ-OAc)Dy4 (μ4 -H2 O)] (2 ), [LZn(μ-OAc)Tb4 (μ4 -H2 O)] (3 ), [LZn(μ-OAc)Ho4 (μ4 -H2 O)] (4 ), [L = Fe[(C5 H4 )–C(Me){N–N{C6 H3 -( o -O)( m -O)]2 ] were synthesized and characterized.2 and3 crystallize in the monoclinic crystal system in the I 2/ m space group, whereas4 crystallizes in the tetragonal crystal system in the I 4/ m space group. The tetra deprotonated ligand L 4− has two distinct coordination compartments: one pocket (2N, 2O) suitable for the transition metal (3d) ions and another pocket (4O) suitable for lanthanide (4f) metal ions. Additionally, the terminal phenoxo group can be utilized for cluster expansion. In all the complexes, the Zn II ion is in a perfect square pyramidal (2N, 3O) geometry whereas the lanthanide ion has a coordination number of eight (8O) in a distorted biaugmented trigonal-prism geometry. The electrochemical properties of2 and3 along with ligand H4 L (1 ) were studied by cyclic voltammetry (CV). All the complexes display a similar type of electrochemical behavior viz ., one quasi-reversible oxidation typical of a ferrocene/ferrocenium motif. The magnetic properties of all the complexes have also been investigated.